Pendidikan Akhlak dalam Al-Qur'an (Kajian Surat al-Hujurah Ayat 11-13) - Moh. Irfan (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
Al-Qur'an is the holy book of Islam which is loaded with the principles of life including moral education. This study aims to examine al-Qur'an verses 11-13 al-Hujurat about moral education and its application in people's lives. This type of research is library research, using documentary data collection methods and data analysis methods using content analysis. The results showed that moral education in the Koran al-Hujurat verses 11-13 include: Uphold the honor of Muslims, repentance, positive thinking, ta'aruf and egalitarian (equality). The application in social life is carried out through exemplary methods, advice, stories, lectures, habituation, warnings and threats (tarhib).